2016
DOI: 10.1016/j.dib.2016.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of mRNA levels for dopaminergic receptors, adrenoceptors and tyrosine hydroxylase in lymphocytes from subjects with clinically isolated syndromes

Abstract: This data article presents a dataset of mRNA levels for dopaminergic receptors, adrenoceptors and for tyrosine hydoxylase, the rate-limiting enzyme in the synthesis of catecholamines, in peripheral blood mononuclear cells as well as in CD4+ T effector and regulatory cells from subjects with clinically isolated syndromes (CIS), which is a first episode of neurological disturbance(s) suggestive of multiple sclerosis. CIS subjects are divided into two groups according to their eventual progression, after 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…Data obtained from the ex vivo animal model support the hypothesis of a direct involvement of DR‐operated pathways in the observed ability of DA to affect PMN functions and of a predominant involvement of the D 1 ‐like DR family (in particular DR D5) in agreement with other studies showing a dysregulation of DR in different human diseases such as MS or PD [11, 15, 18, 19, 21, 53]. In PMN isolated from the bone marrow of DRD5KO mice we showed that DA lacked the ability to prevent fMLP‐induced migration while, on the contrary, this ability was preserved in cells from WT mice; additionally, the key functional role of dopaminergic pathways was suggested also by the reduced PMN count in spleens from DRD5KO mice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Data obtained from the ex vivo animal model support the hypothesis of a direct involvement of DR‐operated pathways in the observed ability of DA to affect PMN functions and of a predominant involvement of the D 1 ‐like DR family (in particular DR D5) in agreement with other studies showing a dysregulation of DR in different human diseases such as MS or PD [11, 15, 18, 19, 21, 53]. In PMN isolated from the bone marrow of DRD5KO mice we showed that DA lacked the ability to prevent fMLP‐induced migration while, on the contrary, this ability was preserved in cells from WT mice; additionally, the key functional role of dopaminergic pathways was suggested also by the reduced PMN count in spleens from DRD5KO mice.…”
Section: Discussionsupporting
confidence: 89%
“…Data obtained from the ex vivo animal model support the hypothesis of a direct involvement of DR-operated pathways in the observed ability of DA to affect PMN functions and of a predominant involvement of the D 1 -like DR family (in particular DR D5) in agreement with other studies showing a dysregulation of DR in different human diseases such as MS or PD [11,15,18,19,21,53].…”
Section: Ex Vivo Studies In Ko Micesupporting
confidence: 89%
See 2 more Smart Citations